High-efficient engineering of osteo-callus organoids for rapid bone regeneration within one month. (September 2022) - Xie, Chang; Liang, Renjie; Ye, Jinchun; Peng, Zhi; Sun, Heng; Zhu, Qiuwen; Shen, Xilin; Hong, Yi; Wu, Hongwei; Sun, Wei; Yao, Xudong; Li, Jiajin; et al.
Abstract: Large bone defects that cannot form a callus tissue are often faced with long-time recovery. Developmental engineering-based strategies with mesenchymal stem cell (MSC) aggregates have shown enhanced potential for bone regeneration. However, MSC aggregates are different from the physiological callus tissues, which limited the further endogenous osteogenesis. This study aims to achieve engineering of osteo-callus organoids for rapid bone regeneration in cooperation with bone marrow-derived stem cell (BMSC)-loaded hydrogel microspheres (MSs) by digital light-processing (DLP) printing technology and stepwise-induction. The printed MSC-loaded MSs aggregated into osteo-callus organoids after chondrogenic induction and showed much higher chondrogenic efficiency than that of traditional MSC pellets. Moreover, the osteo-callus organoids exhibited stage-specific gene expression pattern that recapitulated endochondral ossification process, as well as a synchronized state of cell proliferation and differentiation, which highly resembled the diverse cell compositions and behaviors of developmentally endochondral ossification. Lastly, the osteo-callus organoids efficiently led to rapid bone regeneration within only 4 weeks in a large bone defect in rabbits which need 2–3 months in previous tissue engineering studies. The findings suggested that in vitro engineering of osteo-callus organoids with developmentally osteogenic properties is a promising strategy for rapid bone defect regeneration and recovery.